2017
DOI: 10.1111/1750-3841.13594
|View full text |Cite
|
Sign up to set email alerts
|

Degrees of Antioxidant Protection: A 2‐Year Study of the Bioactive Properties of Organic Milk in Poland

Abstract: The aim of this study was to determine the nutritional value of organic milk in Poland, investigate the influence of diet on antioxidant capacity and degree of antioxidant protection (DAP), and to examine the effect of season on the bioactive properties of milk from organic farms. From 2014 to 2015, 820 milk samples were collected from 6 organic farms during indoor feeding season (IDS) and pasture feeding season (PS). Pasture feeding season + corn grain (PSCG) cows' daily ration during pasture feeding season w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…Puppel et al . () showed that the supplementation of the basic ration with corn grain improved antioxidant capacity and the degree of antioxidant protection in milk. The degree of antioxidant protection and total antioxidant status values were at the highest level when pasture herbage was dominant in the feeding treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Puppel et al . () showed that the supplementation of the basic ration with corn grain improved antioxidant capacity and the degree of antioxidant protection in milk. The degree of antioxidant protection and total antioxidant status values were at the highest level when pasture herbage was dominant in the feeding treatment.…”
Section: Resultsmentioning
confidence: 99%
“…DAP was calculated from the molar ratio between antioxidants and oxidants according to Puppel et al [ 21 ] from Pizzoferrato et al [ 30 ] Where: AC i is the antioxidant compound, OT is the oxidation target (cholesterol) and i is the number of components.…”
Section: Methodsmentioning
confidence: 99%
“…Cholesterol oxidation products (PUCHs) are highly toxic and highly reactive substances which initiate the free radical processes that may result in atherogenic and cancerous lesions. The most bioactive of these are: b-sitosterol (5-cholesten-24bethyl-3b-ol), campesterol (5-cholesten-24b-methyl-3b-ol), and stigmasterol (5,22-cholestadien-24-ethyl-3b-ol) [ 19 , 21 ]. Whole milk contains 20–30 mg PUCh/kg [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…On this subject, it is worth mentioning a similar result described in a recent work of Puppel et al [29], who applied the same index (DAP) to determine the nutritional value of milk produced in Poland during the indoor feeding season, the pasture feeding season, and the pasture feeding season with added corn grain. The results of Puppel et al [29] proved that the content of fat-soluble vitamins (vitamin E, A, and beta-carotene) showed the highest values in milk from cows fed with pasture and pasture with added corn grain: as a result, the DAP index and the total antioxidant status (TAS) values were highest in these milks.…”
Section: Organic Vs Conventional Milk: Focus On Fat Fraction and Minmentioning
confidence: 71%
“…The results of Puppel et al [29] proved that the content of fat-soluble vitamins (vitamin E, A, and beta-carotene) showed the highest values in milk from cows fed with pasture and pasture with added corn grain: as a result, the DAP index and the total antioxidant status (TAS) values were highest in these milks. Likewise, some authors [13,30] verified that concentrations of fat-soluble vitamins (alpha-tocopherol and carotenoids) were considerably higher in milk from low-input farming systems than in milk from high-input systems.…”
Section: Organic Vs Conventional Milk: Focus On Fat Fraction and Minmentioning
confidence: 99%